2020
DOI: 10.1186/s12870-020-02543-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate tolerance genes to low-temperature during maize germination by GWAS and RNA-seq approaches

Abstract: Background Maize ( Zea mays L.) is one of the main agricultural crops with the largest yield and acreage in the world. However, maize germplasm is very sensitive to low temperatures, mainly during germination, and low temperatures significantly affect plant growth and crop yield. Therefore, the identification of genes capable of increasing tolerance to low temperature has become necessary. Results In this study, fourteen phenotypic traits rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
67
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 52 publications
1
67
0
2
Order By: Relevance
“…As shown in Table 2 , five SNPs (PZE-102118136, PZE-102193367, PZE-105052784, PZE-105056721 and PZE-107018981) that were associated with RRS, SL, TG, SG, and SG, respectively, by this study situated within the QTL for maize chilling-related seedling reported previously ( Leipner et al, 2008 ). An overlap of LD regions existed between the significant SNP PZE-108063385 (Chr8:113,291,192) in our study and the cold germination-associated SNP PZE-108064544 (Chr8:113,952,611) reported by Zhang et al (2020a) ; Zhang et al (2020a) . Four associated SNPs (SYN19853, PZE-103096466, PZE-104042136, and PZE-107018981) in this study resided in the previously reported QTL controlling root and shoot traits of maize seedlings under cold stress.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…As shown in Table 2 , five SNPs (PZE-102118136, PZE-102193367, PZE-105052784, PZE-105056721 and PZE-107018981) that were associated with RRS, SL, TG, SG, and SG, respectively, by this study situated within the QTL for maize chilling-related seedling reported previously ( Leipner et al, 2008 ). An overlap of LD regions existed between the significant SNP PZE-108063385 (Chr8:113,291,192) in our study and the cold germination-associated SNP PZE-108064544 (Chr8:113,952,611) reported by Zhang et al (2020a) ; Zhang et al (2020a) . Four associated SNPs (SYN19853, PZE-103096466, PZE-104042136, and PZE-107018981) in this study resided in the previously reported QTL controlling root and shoot traits of maize seedlings under cold stress.…”
Section: Discussionsupporting
confidence: 47%
“…Hu et al detected the genetic elements of chilling tolerance during maize seed germination using GWAS, revealing 17 genetic loci and 18 candidate genes associated with cold tolerance ( Hu et al, 2017 ). In a panel of 222 maize inbred lines, 30 SNPs were associated with low-temperature tolerance during maize seed germination ( Zhang et al, 2020a ). To better understand the genetic architecture of chilling tolerance in maize, we compared the physical positions of the genetic loci between the present study and the previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…RNA-Seq is an important tool for studying gene expression in the whole genome ( Tai et al, 2016 ). However, it is difficult to identify potentially key genes because RNA-Seq usually yields a large number of DEGs ( Zhang et al, 2020 ). In the present study, the blue and turquoise modules had strong correlations with PH and SD, respectively, even though the two modules contained thousands of genes.…”
Section: Discussionmentioning
confidence: 99%
“…Low-temperature stress often occurs at the germination stage, which retards the seedling emergence of spring maize. Maize is vulnerable to low-temperature stress at the germination stage and the early stage of seedling establishment (Zhang et al, 2020). Deciphering the mechanism underlying maize seed germination in response to low-temperature stress can help for improving low-temperature resistance.…”
Section: Discussionmentioning
confidence: 99%